Smallwood Interview 01 - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Division of Educational Technology., 1983)
Robert Pitt talks with Joseph (Joey) Smallwood about what it means to be an "islander". Also speaks about Canadian unity and what a great gift it is to be Canadian.